Pengaruh Kualitas Produk dan Harga terhadap Pengambilan Keputusan Pembelian Baju “Klambiku.Kids” di Kota Madiun - Amalina, Fania Nur; Apriliani, Mifta Putri; Putri, Tiara Natasia; Masruroh, Umma; Anwar, Rosyida Nurul (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research aims to analyze the influence of product quality and price on purchasing decisions for "Kambiku.kids" clothes with icons typical of Madiun culture and art. Variable X is product quality and price, while the dependent variable is the decision to purchase "Klambiku.kids" clothes. The population of this study was 36 respondents. This research uses the classic assumption test which consists of the normality test, multicolliarity test, heroscadicity test and Multiple Regression Test, t test and f test. The results of product quality research have a positive and significant effect on purchasing decisions. Price has a positive and significant effect on purchasing decisions. Based on the results of this research, it is known that the price and quality of the product have a significant contribution in attracting consumers' interest in buying clothes with the "Klambiku.Kids" brand. Clothes with icons and typical Madiun culture. Therefore, sellers need to maintain the image that has been formed so far and develop new, different innovations.